The scholar and the last faerie door - Parry, H. G. (Redhook, 2024)
"All they needed to break the world was a door, and someone to open it. 1921. Years after a botched spell lets loose a faerie into our world, killing hundreds, the study of faerie magic is banned. But for those who survived, their wounds cannot be fixed by bandages and bedrest. A magical curse requires a magical solution. Clover is determined to find a way to save her brother, Matthew--one of the few survivors of the faerie attack. At Camford, England's premier magical academy, she's nobody, just a scholarship witch with no lineage and no connections. But when she catches the eye of golden boy Alden Lennox-Fontaine and his friends, doors that had been previously closed to her are flung open, and she finds herself enmeshed in the glittering and seductive world of the country's magical aristocrats. The summer she spends in Alden's orbit leaves a fateful mark: months of joyous friendship and mutual study come crashing down when experiments go awry, and old secrets are unearthed. Years later, when the faerie seals break again, Clover knows it's because of what they did. And she knows that she must seek the help of people she once called friends--and now doesn't quite know what to call--if there's any hope of saving the world as they know it"--